Reduced vascular perfusion density in idiopathic epiretinal membrane compared to macular pseudohole - Pierro, Luisa; Iuliano, Lorenzo; Marchese, Alessandro; Arrigo, Alessandro; Rabiolo, Alessandro; Bandello, Francesco (International ophthalmology, 2019)
Purpose To investigate the retinal capillary perfusion density by means of optical coherence tomography angiography (OCT-A) in idiopathic epiretinal membrane (ERM) and macular pseudoholes (MPH). Methods This observational cross-sectional study examined consecutive patients affected by ERM and MPH presenting between June 2017 and December 2017, as well as the 30 eyes of 30 healthy subjects. All patients underwent swept-source OCT-A examination. For each patient, vessel perfusion density and foveal avascular zone (FAZ) area were measured. Results Twenty-five eyes of 20 patients with ERM and 28 eyes of 24 patients with MPH were enrolled. Thirty eyes of 30 age-matched healthy controls were included. The perfusion density in the superficial capillary plexus (SCP) of ERM (0.401 ± 0.012) turned out to be inferior that MPH (0.419 ± 0.018) and controls (0.415 ± 0.017) ( p < 0.01), while no significant differences were evident among the three subgroups in the deep capillary plexus (DCP) ( p = 0.1). The FAZ area in the SCP was smaller in the ERM group (0.168 ± 0.123 mm 2 ), respectively, than MPH (0.295 ± 0.013 mm 2 ) and controls (0.213 ± 0.107 mm 2 ) ( p < 0.01), otherwise no difference were noted in the DCP ( p = 0.14). Conclusions OCT-A morphological features differ between idiopathic ERM and MPH, showing lower perfusion density in idiopathic ERM compared to MPH.